DAÑOS, EFECTOS Y AMENAZA DE TSUNAMIS EN AMÉRICA CENTRAL - Fernández A., Mario (2011)
There have been 49 tsunamis in Central America since 1539 to 2000, 37 were in the Pacific and 12 in the Caribbean. Ten of them have a specific damage report, seven in the Pacific and the rest in the Caribbean. The total number of casualties due to local tsunamis is less than 500 but this number could be higher. Themain earthquake sources related to the reported tsunamis are the Cocos-Caribbean subduction Zone, the Polochic-Motagua-Swan Fault System and the North Panama Deformed Belt.An empirical estimation of tsunami hazard for Central America suggests that areas with higher tsunami poten-tial in the Pacific are the coasts from Nicaragua to Guatemala and Central Costa Rica; on the Caribbean side,Honduras Gulf Zone and the coasts of Panama and Costa Rica have a major hazard. Earthquakes of magnitudelarger than 7 with epicenters offshore or onshore (close to the coastline) could trigger tsunamis that would impact those zones.